Blunt splenic injury: are early adverse events related to trauma, nonoperative management, or surgery? - Julien Frandon; Mathieu Rodiere; Catherine Arvieux; Anne Vendrell; Bastien Boussat; Christian Sengel; Christophe Broux; Ivan Bricault; Gilbert Ferretti; Frédéric Thony (Diagnostic and Interventional Radiology, 2015)

(untitled)
PURPOSEWe aimed to compare clinical outcomes and early adverse events of operative management (OM), nonoperative management (NOM), and NOM with splenic artery embolization (SAE) in blunt splenic injury (BSI) and identify the prognostic factors.METHODSMedical records of 136 consecutive patients with BSI admitted to a trauma center from 2005 to 2010 were retrospectively reviewed. Patients were separated into three groups: OM, NOM, and SAE. We focused on associated injuries and early adverse events. Multivariate analysis was performed on 23 prognostic factors to find predictors.RESULTSThe total survival rate was 97.1%, with four deaths all occurred in the OM group. The spleen salvage rate was 91% in NOM and SAE. At least one adverse event was observed in 32.8%, 62%, and 96% of patients in NOM, SAE, and OM groups, respectively (P < 0.001). We found significantly more deaths, infectious complications, pleural drainage, acute renal failures, and pancreatitis in OM and more pseudocysts in SAE. Six prognostic factors were statistically significant for one or more adverse events: simplified acute physiology score 2 ≥25 for almost all adverse events, age ≥50 years for acute respiratory syndrome, limb fracture for secondary bleeding, thoracic injury for pleural drainage, and at least one associated injury for pseudocyst. Adverse events were not related to the type of BSI management.CONCLUSIONPatients with BSI present worse outcome and more adverse events in OM, but this is related to the severity of injury. The main predictor of adverse events remains the severity of injury.